Cilindro espesso curvo submetido a carregamentos combinados no plano de momento fletor, força normal e força cisalhante - Barbosa, Marcelo Luiz Ligeiro (2017)
Thick-walled curved cylinder, most used in oil and gas industry, is one of the most important component of the connector used to make and maintain a connection between flexible flowlines and subsea equipment. However, there is no a standard acceptance criteria for evaluation excessive yielding caused by the loads imposed by flexible flowlines in the curved cylinder component of the connector. The objective of this study is to evaluate the thick-walled curved cylinder behavior under combined tension, shear and bending loads imposed by flexible flowlines in order to establish an acceptance criterion for plastic deformation. The behavior was evaluated by numerical analysis using the finite element method. In this study, loads that caused excessive plastic deformations as well as structural stability lost were identified and an acceptance criterion for plastic deformations was defined.